Computational Fluid Dynamics (CFD) Simulation of Mesh Jet Devices for Promising Energy-Saving Technologies - Yuri A. Sazonov; Mikhail A. Mokhov; Inna V. Gryaznova; Victoria V. Voronova; Khoren A. Tumanyan; Mikhail A. Frankov; Nikolay N. Balaka (Salehan Institute of Higher Education, 2022)
This paper discusses the development of mesh jet devices for hybrid turbines, including developing Euler's ideas, and considers a new patented version of a mesh jet device designed to create guiding devices for turbines. The research methods are based on simulations using CFD and additive technologies. An intermediate conclusion is that a new scientific direction for the study and creation of mesh jet control systems has been formed as part of developing Euler's ideas. Calculation methods showed possible improvements in the performance of jet devices, including the use of curved tubes proposed by Euler to create turbines. This study shows that at the nozzle or mixing chamber outlet, the jet can deflect by an angle from +180° to -180° within the geometric sphere. This study also shows that the scientific groundwork prepared by Euler is not yet fully understood. The ongoing research mainly focuses on creating multi-mode jet devices designed for control systems for mesh turbomachines. Here, power consumption from an external source can be reduced to save energy. Some results of ongoing studies can also be applied in other industries (for example, when creating hybrid propulsion systems or propulsors). The scientific novelty of this work consists of improving the design methodology of jet machinery and turbomachines. Doi: 10.28991/CEJ-2022-08-12-06 Full Text: PDF